224 EFFECT OF COMBINED ADMINISTRATION OF RECOMBINANT HUMAN GROWTH HORMONE AND TESTOSTERONE ON ERYTHROPOIESIS. (10th December 2015) - Ham, M.; Yan, X.; Cohan, P.; Korenman, S.
Abstract : Testosterone (T) and growth hormone (GH) have been shown to increase erythropoiesis when administered separately. Due to the dearth of information regarding the effects of combined GH and T, the increasing numbers of people receiving both hormones and the cardiovascular risks associated with elevated hematocrit, we decided to investigate whether rhGH and T had additive effects on erythropoiesis. We conducted a retrospective chart review of 52 male patients. The variable group consisted of 14 hypopituitary patients treated with rhGH and T, and the two control groups were hypopituitary and nonpituitary hypogonadal patients receiving testosterone, composed of 14 and 24 men, respectively. A Mixed Model statistical analysis was utilized to compare the hematocrits and hemoglobins of the groups. There were no significant differences between the average hematocrits of all groups. The variable and hypogonadal group were found to have significant rates of increase in hematocrit, with the variable group exhibiting the fastest increase. All patients were monitored carefully for increases in hematocrit, which led to decreases in treatment dosage, thus accounting for the similar averages of hematocrit. Patients treated with rhGH and T had a significantly higher rate of increase, demonstrating the synergistic effect of both hormones on erythropoiesis.